2021
DOI: 10.3390/vetsci8080167
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Snail Secretion Filtrate in an Experimental Model of Excisional Wounds in Mice

Abstract: Wound healing is a physiological process comprising several coordinated phases, such as inflammation, proliferation, and remodeling. For centuries, Helix aspersa Muller mucus has been known to have biological properties that are useful for treating skin disorders. In this study, we used a full-thickness excisional wound model in mice to test the hypothesis that Snail Secretion Filtrate (SSF) can improve the wound healing process. The mucus from Helix aspersa Muller was obtained mechanically by manually stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
(45 reference statements)
0
7
0
1
Order By: Relevance
“…In mouse models, snail secretory filtrate (SSF) significantly increased the rate and percentage of wound area closure and COL3A1 level and decreased MPO expression in the wound and IL-1β. Moreover, TNF-α expression levels of the restorative growth factor TGF-β in wounds level up, suggesting an enhancement of the adaptive wound healing process (Gugliandolo et al, 2021). This illustrates that snail extract is a safe and effective alternative therapy for wound healing (Tsoutsos et al, 2009).…”
Section: Snail Mucinsmentioning
confidence: 92%
See 1 more Smart Citation
“…In mouse models, snail secretory filtrate (SSF) significantly increased the rate and percentage of wound area closure and COL3A1 level and decreased MPO expression in the wound and IL-1β. Moreover, TNF-α expression levels of the restorative growth factor TGF-β in wounds level up, suggesting an enhancement of the adaptive wound healing process (Gugliandolo et al, 2021). This illustrates that snail extract is a safe and effective alternative therapy for wound healing (Tsoutsos et al, 2009).…”
Section: Snail Mucinsmentioning
confidence: 92%
“…In general, Ginsenosides Rb1 (Zhang et al, 2021), Lupeol (Pereira Beserra et al, 2020), garlic acid (Singh et al, 2019), Ferulic acid (Dwivedi et al, 2022), Hesperdin (Jagetia and Rao, 2022), Aloin (Liu et al, 2015), Simmondsia cheinensis (Ranzato et al, 2011), Snail mucins (Gugliandolo et al, 2021), Angelica Sinensis ethanol extract (Bai et al, 2012b), Apigenin (Choi et al, 2016)have important potential to promote wound healing, and the molecular mechanism should be further studied. This conclusion is supported by desirable results, both in animal and cell experiments.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…The use of snail slime in the cosmetic field is now recognized for the following properties that distinguish it: emollient, lubricant and protective. In addition to the aforementioned peculiarities and characteristics, snail slime is also characterized by its antimicrobial [ 32 ] and healing effects [ 15 , 33 ]. There are several findings that demonstrate the absence of cytotoxicity in different cell lines, such as in human keratinocytes (HaCaT), human dermal fibroblasts (MRC-5) and murine embryo fibroblasts (NIH-3T3) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under the great umbrella of natural substances, our attention was focused on snail slime. Previous studies, conducted in our laboratories, have shown that snail slime, secreted by the snail Helix aspersa Muller, has strong anti-inflammatory activity, demonstrated in in vivo studies [ 15 , 16 ]. The idea of using mucus or snail secretion has its roots in the history of humans, when in ancient times, the mucus was used for the management of skin disorders; today, it is proposed as a component for the formulation of parapharmaceutical products for wound management and as a constituent of cosmetic products.…”
Section: Introductionmentioning
confidence: 99%
“…It is an integrated process of damage and anti-damage ( Elkahloun et al, 2019 ; De Meij et al, 2021 ). In the process of inflammation, damaging factors directly or indirectly cause tissue and cell damage; the damaged tissues or cells dilute and kill damaging factors through inflammatory congestion and exudation; simultaneously, damaged tissue can be repaired and healed through the regeneration of parenchymal and interstitial cells ( Hu et al, 2020 ; Zhang et al, 2021 ; Gugliandolo et al, 2021 ; Maria, 2021 ; Sophie et al, 2022 ). Inflammation can manifest as either acute or chronic.…”
Section: Introductionmentioning
confidence: 99%